Determinan yang Mempengaruhi Kualitas Audit dengan Due Professional Care Sebagai Variabel Intervening Pada Inspektorat Daerah Kota Palembang - Tiara Septiani; Periansya; M. Husni Mubarok (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the direct and indirect influence of Competency, Accountability, and Time Budget Pressure on Audit Quality through Due Professional Care as an Intervening Variable. This research is quantitative research, using primary data in the form of a questionnaire. The population in this study was 61 Palembang City Regional Inspectorate Auditors, using simple random sampling, so there were 38 samples. The data analysis technique used is multiple linear regression, using SPSS version 2.6 software as a hypothesis testing tool. The research results show that Competency has no direct effect on Due Professional Care, Accountability and Time Budget Pressure have an effect on Due Professional Care, Competency and Due Professional Care have an effect on Audit Quality, Accountability and Time Budget Pressure have no effect on Audit Quality. Simultaneously Competence, Accountability and Time Budget Pressure influence Due Professional Care, and indirectly Competency, Accountability and Time Budget Pressure influence Audit Quality through Due Professional Care.